A radiomics model can distinguish solitary pulmonary capillary haemangioma from lung adenocarcinoma. (14th October 2021) - Wang, Hao-Jen; Lin, Mong-Wei; Chen, Yi-Chang; Chen, Li-Wei; Hsieh, Min-Shu; Yang, Shun-Mao; Chen, Ho-Feng; Wang, Chuan-Wei; Chen, Jin-Shing; Chang, Yeun-Chung; Chen, Chung-Ming
Abstract: : OBJECTIVES: Solitary pulmonary capillary haemangioma (SPCH) is a benign lung tumour that presents as ground-glass nodules on computed tomography (CT) images and mimics lepidic-predominant adenocarcinoma. This study aimed to establish a discriminant model using a radiomic feature analysis to distinguish SPCH from lepidic-predominant adenocarcinoma. METHODS: In the adenocarcinoma group, all tumours were of the lepidic-predominant subtype with high purity (>70%). A classification model was proposed based on a two-level decision tree and 26 radiomic features extracted from each segmented lesion. For comparison, a baseline model was built with the same 26 features using a support vector machine as the classifier. Both models were assessed by the leave-one-out cross-validation method. RESULTS: This study included 13 and 49 patients who underwent complete resection for SPCH and adenocarcinoma, respectively. Two sets of features were identified for discrimination between the 2 different histology types. The first set included 2 principal components corresponding to the 2 largest eigenvalues for the root node of the two-level decision tree. The second set comprised 4 selected radiomic features. The area under the receiver operating characteristic curve, accuracy, sensitivity, specificity were 0.954, 91.9%, 92.3% and 91.8% in the proposed classification model, and were 0.805, 85.5%, 61.5% and 91.8% in the baseline model, respectively. The proposed classification model significantly outperformed the baseline model ( P < 0.05). CONCLUSIONS: The proposed model could differentiate the 2 different histology types on CT images, and this may help surgeons to preoperatively discriminate SPCH from adenocarcinoma. Abstract : Solitary pulmonary capillary haemangioma (SPCH) is a primary benign lung tumour that exhibits proliferation of capillaries in the alveolar septa [1].